Three-dimensional kinestatic analysis of McPherson front suspension with steering and caster angle input - Eidt, Rafael Henrique Fank (2025)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Mecânica, Florianópolis, 2025.